Changes in body mass index during childhood and risk of various asthma phenotypes: a retrospective analysis. Issue 3 (6th March 2017) - Chastang, Julie; Baiz, Nour; Parnet, Laure; Cadwallader, Jean Sébastien; De Blay, Frédéric; Caillaud, Denis; Charpin, Denis André; Dwyer, John; Lavaud, François; Raherison, Chantal; Ibanez, Gladys; Annesi‐Maesano, Isabella
Abstract: Background: It is known that asthma is related to obesity but also to small birthweight. The objective of this study was to clarify this issue by assessing the putative relationship between the changes in corpulence between birth and childhood as assessed by body mass index (BMI) and asthma phenotypes. Methods: The following status in corpulence was assessed in 7781 schoolchildren using quartile of BMI at birth and at around 10 (9–11 years): underweight at birth and at around 10, underweight at birth and overweight at around 10, overweight at birth and underweight at around 10, overweight at birth and at around 10, and the reference group constituted by all the other children in whom corpulence changes were not extreme. Determination of asthma phenotypes (allergic, non‐allergic, and exercise‐induced asthma) was based on a clinical examination including skin prick tests, an exercise challenge test, and a questionnaire. Results: The risk of allergic asthma was higher in children with persistent underweight, children with persistent overweight, and children becoming markedly more corpulent. In boys, the risk of allergic asthma was significantly higher for the less corpulent children at birth, regardless of whether they remained so or become overweight. In girls, the risk of allergic asthma was significantly higher in those with persistent overweight. There were no significant associations between BMI changes and non‐allergic and exercise‐induced asthma. Conclusions: We observed that some extreme changes in BMI, persistent underweight, and persistent overweight in childhood increased the risk of allergic asthma.